The life-changing magic of tidying up : the Japanese art of decluttering and organizing - Kondo, Marie (Ten Speed Press, 2014)
This best-selling guide to decluttering your home from Japanese cleaning consultant Marie Kondo takes readers step-by-step through her revolutionary KonMari Method for simplifying, organizing, and storing.